Study on the characteristics and mechanism of inert powder inhibition of gas/coal dust compound explosion - Wentao JI; Guotao ZHANG; Shuaishuai YANG; Zihui XU; Wenzhe MAO; Yan WANG (Meitan kexue jishu)
Gas/coal dust composite explosion is a complex process that combines homogeneous and heterogeneous combustion. The combustion main control mechanism changes dynamically and the explosion mechanism is more complex, resulting in higher explosion sensitivity and explosion intensity compared to single-phase gas or coal dust explosion, which seriously restricts the safe production of coal mines. In order to prevent and control the gas/coal dust composite explosion disaster, two inert powders, sodium bicarbonate and calcium carbonate, are selected to conduct experiments on inert powder suppression of gas/coal dust composite explosions in a 20 L spherical explosion device. Based on the different concentration ratios of gas and coal dust, the inhibition effect of two inert powders on the maximum explosion pressure and the maximum explosion pressure rise rate of the gas/coal dust composite system are analyzed and compared, as well as the differences and connections between the inhibition effect of the two inert powders. And the inhibition efficiency and mechanism of the two inert powders on gas/coal dust composite explosions are reflected comprehensively. The research results indicate that sodium bicarbonate and calcium carbonate have an inhibitory effect on the explosion of gas/coal dust composite systems with different concentration ratios. Sodium bicarbonate can not only suppress the explosion of gas/coal dust composite by physical suppression methods such as decomposing heat absorption, delaying coal dust pyrolysis, and reducing coal dust decomposition rate, but also by chemical suppression methods that consume key free radicals in the explosion reaction, however, calcium carbonate can only suppress explosions through physical heat absorption, so the inhibitory effect of sodium bicarbonate on the explosion of gas/coal dust composite system is better than that of calcium carbonate. Specifically, sodium bicarbonate can completely suppress all working conditions, while calcium carbonate can only completely suppress the gas/coal dust composite working conditions when the gas concentration is below 8%. In addition, the suppression efficiency of two inert powders on the explosion pressure of the gas/coal dust composite system first increases and then decreases with the increase of gas concentration in the system. The suppression efficiency is highest when the gas concentration is 6% and the coal dust concentration is 100 g/m3; The suppression efficiency of the explosion pressure rise rate of the gas/coal dust composite system gradually increases with the increase of gas concentration in the system, and the suppression efficiency is highest for pure gas explosions with a concentration of 10%.